Priority Sequence Analysis of Local Primary Road Bridge Infrastructure Handling Using AHP and TOPSIS Methods in Bojonegoro Regency - Arik Nur Cahyo; Esti Wulandari; Andi Patriadi (Jurnal Teknik Indonesia, 2026)
Optimal management of bridge infrastructure requires effective planning and implementation. Currently, bridge maintenance prioritization in Bojonegoro Regency faces challenges due to budget limitations resulting from central government efficiency policies. Therefore, selecting priority bridges from the list proposed in the budget implementation document is essential to ensure that bridge maintenance programs managed by the Public Works and Spatial Planning Office are implemented efficiently and appropriately. This study aimed to analyze the priority sequence for handling primary local road bridge infrastructure in Bojonegoro Regency by considering various aspects and criteria objectively. Among various decision-making methods, the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) were considered suitable approaches because they assist in solving complex decision-making problems by organizing criteria and alternatives into a hierarchical structure. The results of the AHP and TOPSIS analyses showed different priority rankings for bridge handling. Based on the AHP method, the priority order was Bridge Sambeng–Kedewan 19, Bridge Sambeng–Besah 5, Bridge Sumberrejo–Kepohkidul 2, Bridge Watujago–Bobol 3, Bridge Sidobandung–Sepat 6, and Bridge Kapas–Sampang 1. Meanwhile, the TOPSIS method produced the priority order of Bridge Sambeng–Kedewan 19, Bridge Watujago–Bobol 3, Bridge Sambeng–Besah 5, Bridge Sumberrejo–Kepohkidul 2, Bridge Sidobandung–Sepat 6, and Bridge Kapas–Sampang 1.